The Comparison of Inflammatory Responses and Clinical Results After Groin Hernia Repair Using Polypropylene or Polyester Meshes - Bulbuller, N.; Kirkil, C.; Godekmerdan, A.; Aygen, E.; Ilhan, Y. S. (Springer India, 2015)
The aim of this study was to compare the clinical results and the inflammatory responses against polypropylene and polyester meshes after groin hernia repair. Ninety patients with unilateral inguinal hernia randomly underwent Shouldice herniorrhaphy or Lichtenstein hernioplasty using polypropylene or polyester meshes. Venous blood samples were collected to evaluate serum interleukin-6 (IL-6) and C-reactive protein (CRP) levels. Postoperative acute and chronic pain and time to attain to normal activities were evaluated. IL-6 levels decreased to preoperative levels in all groups at 48th hour. CRP levels of mesh-implanted groups are significantly higher than preoperative level at 48th hour, while it reduced to preoperative level in Shouldice herniorrhaphy group. Patients treated with mesh repair had less postoperative acute pain and recovered more rapidly than those who underwent Shouldice herniorrhaphy. It was concluded that polypropylene and polyester meshes used in hernia repair caused similar inflammatory responses and that clinical results after groin hernia repair with these prostheses were not significantly different.
Keywords: Groin hernia; Polypropylene mesh; Polyester mesh; Inflammatory response